1997
DOI: 10.1152/ajplung.1997.272.5.l996
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein A regulates cytokine production in the monocytic cell line THP-1

Abstract: Surfactant lipids inhibit cytokine production by immune cells, and surfactant protein A (SP-A) stimulates it. By enzyme-linked immunosorbent assay and mRNA blotting, we studied proinflammatory cytokine production by the monocytic cell line THP-1. SP-A caused increases in tumor necrosis factor (TNF)-alpha within 1 h, peaking at 4 h and then declining. Interleukin (IL)-1 beta increased and stayed elevated for 24 h. SP-A stimulated IL-8 also, peaking at 4 h, rapidly declining, and peaking again at 24 h. SP-A-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
61
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 0 publications
6
61
1
Order By: Relevance
“…Surfactant protein A (SP-A), a 34-to 36-kDa glycoprotein, plays a major role in the modulation of innate host defense in the lung (7,16,21,41,48,52). SP-A has been shown to stimulate chemotaxis of macrophages (70), enhance phagocytosis (11,34,44,46,47,50,63), induce generation of reactive oxidants (61), regulate the nitric oxide production (1,23), and influence the proliferation of immune cells (2,38) and the production of proinflammatory cytokines (3,27,37,39,68,69). SP-A can bind to receptors on the macrophage membrane (35).…”
mentioning
confidence: 99%
“…Surfactant protein A (SP-A), a 34-to 36-kDa glycoprotein, plays a major role in the modulation of innate host defense in the lung (7,16,21,41,48,52). SP-A has been shown to stimulate chemotaxis of macrophages (70), enhance phagocytosis (11,34,44,46,47,50,63), induce generation of reactive oxidants (61), regulate the nitric oxide production (1,23), and influence the proliferation of immune cells (2,38) and the production of proinflammatory cytokines (3,27,37,39,68,69). SP-A can bind to receptors on the macrophage membrane (35).…”
mentioning
confidence: 99%
“…Human SP-A from bronchoalveolar lavage (BAL) can stimulate cytokine production in the macrophage-like cell line, THP-1, and this effect is inhibited by the surfactant lipids (14,15). SP-A variants expressed in vitro using the baculovirus-mediated expression system stimulate TNF-α production in THP-1 cells.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that SP-A exhibits stimulatory, as well as inhibitory, effects on alveolar macrophages and cells of the monocyte/macrophage lineage. Stimulatory effects of SP-A on these cells include increased oxidative activity (30,34,72,83), increased production of proinflammatory cytokines (43,44), increased expression of cell surface proteins (42), increased matrix metalloproteinase production (79), enhanced chemotaxis in part via directed actin polymerization (76), and enhanced phagocytosis (21a, 48, 75, 84). Inhibitory effects of SP-A include decreased cytokine expression and nitric oxide production in mouse and rat macrophages pretreated with LPS (3,11,51).…”
mentioning
confidence: 99%
“…Using the in vitro O 3 exposure system, we studied the effects of O 3 on lung defense mechanisms by exposing THP-1 cells (a model for alveolar macrophages) to O 3 . Previous work has shown that the THP-1 cell line is a suitable model for such study (4,82,83) and that human SP-A enhances the expression of proinflammatory cytokines and cell surface proteins in THP-1 cells (42,44). Moreover, the ability of recombinant SP-A variants to stimulate cytokine production by THP-1 cells has been shown to be reduced following O 3 exposure of the variants (34,83).…”
mentioning
confidence: 99%